Prediction of persistent post‐operative pain: Pain‐specific psychological variables compared with acute post‐operative pain and general psychological variables. (20th September 2017) - Horn‐Hofmann, C.; Scheel, J.; Dimova, V.; Parthum, A.; Carbon, R.; Griessinger, N.; Sittl, R.; Lautenbacher, S.
Abstract: Background: Psychological variables and acute post‐operative pain are of proven relevance for the prediction of persistent post‐operative pain. We aimed at investigating whether pain‐specific psychological variables like pain catastrophizing add to the predictive power of acute pain and more general psychological variables like depression. Methods: In all, 104 young male patients undergoing thoracic surgery for pectus excavatum correction were studied on the pre‐operative day (T0) and 1 week (T1) and 3 months (T2) after surgery. They provided self‐report ratings (pain‐related: Pain Catastrophizing Scale, Pain Anxiety Symptoms Scale = PASS, Pain Vigilance and Awareness Questionnaire = PVAQ; general psychological: Screening for Somatoform Symptoms, State‐Anxiety Inventory‐X1, Center for Epidemiologic Studies Depression Scale = CES‐D). Additional predictors (T1) as well as criterion variables (T2) were pain intensity (Numerical Rating Scale) and pain disability (Pain Disability Index). Results: Three months after surgery, 25% of the patients still reported clinically relevant pain (pain intensity ≥3) and over 50% still reported pain‐related disability. Acute post‐operative pain as well as general psychological variables did not allow for a significant prediction of persistent post‐operative pain; in contrast, pain‐related psychological variables did. The best single predictors were PASS for pain intensity and PVAQ for pain disability. Conclusions: Pain‐related psychological variables derived from the fear‐avoidance model contributed significantly to the prediction of persistent post‐operative pain. The best possible compilation of these measures requires further research. More general psychological variables may become relevant predictors later in the medical history. Significance: Our results suggest that pain‐specific psychological variables such as pain anxiety and pain hypervigilance add significantly to the prediction of persistent post‐operative pain and might even outperform established predictors such as acute pain and general psychological variables. Clinicians might benefit from the development of time‐economic screening tools based on these variables.